Dynamic Response in Transient Operation of a Variable Geometry Turbine Stage: Influence of the Aerodynamic Performance - Nicolas Binder; Jaime Garcia Benitez; Xavier Carbonneau (International Journal of Rotating Machinery)
The transient response of a radial turbine stage with a variable geometry system is evaluated. Mainly, the consequences of the variations of the aerodynamic performance of the stage on the response time are checked. A simple quasi-steady model is derived in order to formalize the expected dependences. Then an experimental campaign is conducted: a brutal step in the feeding conditions of the stage is imposed, and the response time in terms of rotational speed is measured. This has been reproduced on different declinations of the same stage, through the variation of the stator geometry, and correlated to the steady-state performance of the initial and final operating points of the transient phase. The matching between theoretical expectation and results is surprisingly good for some configurations, less for others. The most important factor identified is the mass-flow level during the transient phase. It increases the reactivity, even far above the theoretical expectation for some configurations. For those cases, it is demonstrated that the quasi-steady approach may not be sufficient to explain how the transient response is set.